Estimation of losses to agricultural crops by the wild animals in Najibabad forest division - RATHI, ROBIN; KUKRETI, MOHAN; BHATT, DINESH (The Indian Journal of Animal Sciences, 2025)
The wild animals cause losses to agriculture crop yields. The present study focuses on the assessment of agricultural damage caused by these wild animals in villages adjacent to protected areas and located in Najibabad forest division in Bijnor (Uttar Pradesh). The results showed that elephant (Elephas maximus) is the most problematic animal responsible for crop raiding followed by nilgai (Boselaphus tragocamelus). The sugarcane fields closer to the forest edge are raided more by elephants in comparison to rice, wheat and vegetables. This study recommended that active participation of stakeholders with the help of forest officials can help in mitigating crop raiding incidences in future.